You are on page 1of 15

# HW 4.

1a # 7, 9 ,15, 19, 23, 27, 29, 33, 35

Transformations
Pre Lesson
If (x – h), then what is the value of h?
(x – 3) (x + 3) (x + p) (x – p) (x – 1)
Find the domain and range.
range

1

D: all real #s between and equal to 1 and 5
R: all real #s between and equal to 2 and 4

2

D: all real #s between and equal to -3 and 3
R: all real #s between and equal to -3 and 3

3

D: all real #s between and equal to 2 and 6
R: all real #s between and equal to -3 and 2

4

D: all real #s ≥ 3
R: all real #s ≥ 2

5

D: all real #s
R: all real #s ≥ 0

6

D: all real #s
R: all real #s ≤ 1

Vertex Form

Hey that’s the h k thing again!

y = a(x – h)2 + k
If a is +, happy
If |a| < 1, wide (½x2)
If |a| > 1, narrow (2x2)
The vertex is the point (h,k).
The h moves the parabola left and right.
The k moves the parabola up and down.

Maximum

(h, k)

Minimum

x=h

Where is the vertex? y = (x – 3)2 + 4

(3, 4)

y = 1(x – 3)2 + 4
y = a(x – h)2 + k

y = (x + 3)2 + 4
y = 1(x – -3)2 + 4
y = a(x – h)2 + k

y = (x – 3)2 – 4

(-3, 4)
(3, -4)

y = 1(x – 3)2 + -4
y = a(x – h)2 + k

y = (x + 3)2 – 4

(-3, -4)

y = 1(x – -3)2 + -4
y = a(x – h)2 + k

y = (x – 3)2

(3, 0)

y = 1(x – 3)2 + 0
y = a(x – h)2 + k

y = x2 + 4

y = 1(x – 0)2 + 4
y = a(x – h)2 + k

(0, 4)

Graph y = 2x2
1. Plot the vertex
(0, 0)

2. Draw the axis of symmetry
x=0

3. Make a table
x
-2
-1
vertex  0
1
2

y
8
2
0
2
8

4. Plot the points

Graph y = x2 + 2 and compare it to y = x2
1. Plot the vertex
(0, 2)

2. Draw the axis of symmetry
x=0

3. Make a table
x
-2
-1
vertex  0
1
2

y
6
3
2
3
6

4. Plot the points

The graph moved 2 units up

Graph y = (x + 2)2 and compare it to y = x2
1. Plot the vertex
(-2, 0)

2. Draw the axis of symmetry
x = -2

3. Make a table
x
-4
-3
vertex  -2
-1
0

y
4
1
0
1
4

4. Plot the points

The graph moved 2 units left

y = –(x – 3)2 + 1
The vertex is
(3, 1)

The axis of symmetry is
x=3

The maximum is
k=1

The domain is
All real #s

The range is
All real #s ≤ 1

Quick Sketch

Now Backwards
Find the equation of the graph.
Use y = a(x – h)2 + k
2 = a(-1 – -3)2 + 4
2 = a(-1 + 3)2 + 4
2 = a(2)2 + 4
2 = a4 + 4
-2 = 4a
-½ = a
Use it again y = a(x – h)2 + k
y = -½(x – -3)2 + 4
y = -½(x + 3)2 + 4

h k
(-3, 4)
x y
(-1, 2)